2016
DOI: 10.2147/copd.s118523
|View full text |Cite
|
Sign up to set email alerts
|

Costs of chronic obstructive pulmonary disease in urban areas of China: a cross-sectional study in four cities

Abstract: PurposeThe economic burden of COPD has not been well studied in China. This study investigated the total costs caused by COPD and the influencing factors for the high economic burden in urban areas of China.Patients and methodsA cross-sectional study was carried out among 678 COPD patients in four cities in China in 2011. The average annual direct medical costs (DMCs), direct nonmedical costs (DNMCs), and indirect costs (ICs) on COPD were measured by median and mean (± standard deviation). Logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 24 publications
2
46
0
Order By: Relevance
“…One study conducted in 2011 in four Chinese cities among 678 patients with COPD found that poorer quality of life as determined by the EuroQol-5 dimensions (EQ-5D) health questionnaire was significantly linked to increased medical costs [40]. A further analysis of this cohort showed the mean annual direct medical (DMC), direct non-medical (DNMC), and indirect (IC) costs per COPD patient were 11, 968 yuan (US$ 1853), 539 yuan (US$ 83), and 2087 yuan (US$ 323), respectively, with over half (56.7%) of total costs due to hospitalization [41]. While these data are somewhat dated, they do offer some degree of insight into the high cost burden of COPD in China and will be interesting to compare with the results from the larger REAL cohort.…”
Section: Discussionmentioning
confidence: 93%
“…One study conducted in 2011 in four Chinese cities among 678 patients with COPD found that poorer quality of life as determined by the EuroQol-5 dimensions (EQ-5D) health questionnaire was significantly linked to increased medical costs [40]. A further analysis of this cohort showed the mean annual direct medical (DMC), direct non-medical (DNMC), and indirect (IC) costs per COPD patient were 11, 968 yuan (US$ 1853), 539 yuan (US$ 83), and 2087 yuan (US$ 323), respectively, with over half (56.7%) of total costs due to hospitalization [41]. While these data are somewhat dated, they do offer some degree of insight into the high cost burden of COPD in China and will be interesting to compare with the results from the larger REAL cohort.…”
Section: Discussionmentioning
confidence: 93%
“…Exacerbations formed the basis of the health states given their importance as drivers of future events [25][26][27][28][29][30] and COPD-related economic costs. [31][32][33][34][35] The model was developed using R programming language (RStudio version 1.1.383, R version 3.4.2).…”
Section: Model Structurementioning
confidence: 99%
“…Of the total global disability-adjusted life-years (DALYs) due to chronic respiratory diseases, 32.0% currently occur in India [6], with COPD in India currently accounting for 4.8% of the total worldwide DALYs [6]. COPD is also associated with considerable economic burden, which is increasing [23][24][25][26][27]. In the US in 2010, the projected annual cost of COPD was $49.9 billion, including $29.5 billion of direct medical costs [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the US in 2010, the projected annual cost of COPD was $49.9 billion, including $29.5 billion of direct medical costs [24]. In China, current annual direct medical costs for COPD are US$30.30 billion, direct non-medical costs are US$1.36 billion, and indirect costs are US$5.28 billion, with hospitalisations accounting for 56.7% of total costs [25]. In Korea, the estimated costs for COPD in 2018 were approximately US$1.245 billion, with direct medical costs accounting for approximately 20% of this cost [23].…”
Section: Introductionmentioning
confidence: 99%